Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/microorganisms10122442
|View full text |Cite
|
Sign up to set email alerts
|

Low Salt Influences Archaellum-Based Motility, Glycerol Metabolism, and Gas Vesicles Biogenesis in Halobacterium salinarum

Abstract: Halobacterium salinarum NRC-1 is an extremophile that grows optimally at 4.3 M NaCl concentration. In spite of being an established model microorganism for the archaea domain, direct comparisons between its proteome and transcriptome during osmotic stress are still not available. Through RNA-seq-based transcriptomics, we compared a low salt (2.6 M NaCl) stress condition with 4.3 M of NaCl and found 283 differentially expressed loci. The more commonly found classes of genes were: ABC-type transporters and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, a study in another halophilic species found that while protein abundance changes for the archaella biosynthetic proteins in the tested experimental conditions were not found, transcriptional analysis was able to identify differences in the regulation of arl genes 35 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, a study in another halophilic species found that while protein abundance changes for the archaella biosynthetic proteins in the tested experimental conditions were not found, transcriptional analysis was able to identify differences in the regulation of arl genes 35 .…”
Section: Discussionmentioning
confidence: 83%
“…While differences in protein abundance of ArlI or ArlJ were not observed in wild type or JK3 25 , the abundance of archaella biosynthetic components could be below the detection level of quantitative proteomics experiment, consistent with the absence of any ArlI or ArlJ peptides identified in the Archaeal Proteome Project (ArcPP) database 34 . However, a study in another halophilic species found that while protein abundance changes for the archaella biosynthetic proteins in the tested experimental conditions were not found, transcriptional analysis was able to identify differences in the regulation of arl genes 35 . Furthermore, another study reported that sessile, disk-shaped biofilm-derived cells can exhibit a decreased expression of arl genes 36 .…”
Section: Discussionmentioning
confidence: 83%
“…The work from Onga and other coauthors that does not include the author of this thesis (Onga et al, 2022), draw one of their main conclusions supported by the TPS map provided by (Ibrahim et al, 2021). In their Figure 3b (Ibrahim et al, 2021) on a third party work (Onga et al 2022). The gene on focus is rpl15e (see text for details).…”
Section: Transcription Processing Sites (Tps)mentioning
confidence: 90%
“…(b) screenshot of a GGB use to visualize public Ribo-seq data and TPS also presented as a resource in (Ibrahim et al, 2021). (c) screenshot of Figure 3 at page 7 from (Onga et al 2022) where the direct usage of visualization (b) was made (see text for details and refer to their paper for full biological interpretation).…”
Section: Transcription Processing Sites (Tps)mentioning
confidence: 99%
See 1 more Smart Citation